Effect of Green Bean Sprout Peels Flour on the Commercial Carcass Pieces of Male Bali Ducks Age 8 Weeks - I P. H., Setyawan; Siti, N W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2019)
The research aimed to determined the effect of green bean sprout peels flour on the commercial carcass pieces of male bali ducks age of 8 weeks carried out at Sesetan farm located on Jalan Raya Sesetan, Gang Markisa, Denpasar, Bali, for 8 weeks starting from february 16 to april 16 2018. The study was carried out using a completely randomize design (CRD) consisting of three treatments, namely: P0 (commercial rations without green bean sprout peels flour), P1 (rations containing 6% green bean sprouts peels flour), and P2 (rations containing 12% green bean peels sprout flour). Each treatment consisted of 5 replications and each replication used 3 heads of male bali ducks aged of 3 days with an average body weight of 42.9 g ± 1.98 g. The variables observed were weight and percentage of breast, thighs, drum stick, wings and back. The results showed that the administration of green bean sprout peels flour at 6% and 12% were not significantly different (P>0.05) for all weights and the percentage of commercial carcass pieces. Based on the results of the study it can be concluded that the administration of green bean sprouts peels flour at level 6% and 12% does not affect on the weight and percentage of commercial carcass pieces (breast, thighs, drum stick, wings and back of male bali ducks aged of 8 weeks.   Keywords: Commersial carcass pieces, male bali ducks, green bean sprout peels flour